1998
DOI: 10.1042/cs0940405
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Changes during Pregnancy and Lactation: A Longitudinal Cohort Study

Abstract: 1. The influence of pregnancy, lactation and weaning on bone mineral density in healthy women was investigated during a 2 year prospective study of 59 pregnant and lactating women from the 18th week of gestation. 2. Bone mineral density was measured by dual energy X-ray absorptiometry at the non-dominant radius ultra distally and more proximally in the 18th and 37th weeks of gestation, and 0, 3, 6, 12 and 18 months after delivery. Measurements of bone mineral density of the lumbar spine, the proximal femur and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
128
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 24 publications
13
128
3
1
Order By: Relevance
“…Other similar studies have also been limited by small sample sizes, with number of lactating subjects ranging from 9 to 26 (Hayslip et al, 1989;Cross et al, 1995;Krebs et al, 1997;Ritchie et al, 1998). This study confirmed previous studies that lactation is associated with a decrease in BMD and this effect is particularly pronounced at the lumbar spine and femoral neck (Kolthoff et al, 1998). This study also showed that the observed decrease in BMD was associated with lactation per se and was not a consequence of the mother having recently been pregnant because such bone changes were not observed in the formula feeding mothers postpartum.…”
Section: Discussionsupporting
confidence: 88%
“…Other similar studies have also been limited by small sample sizes, with number of lactating subjects ranging from 9 to 26 (Hayslip et al, 1989;Cross et al, 1995;Krebs et al, 1997;Ritchie et al, 1998). This study confirmed previous studies that lactation is associated with a decrease in BMD and this effect is particularly pronounced at the lumbar spine and femoral neck (Kolthoff et al, 1998). This study also showed that the observed decrease in BMD was associated with lactation per se and was not a consequence of the mother having recently been pregnant because such bone changes were not observed in the formula feeding mothers postpartum.…”
Section: Discussionsupporting
confidence: 88%
“…A few studies have measured peripheral sites using DXA during pregnancy. Some showed a significant change in bone mineral at the distal radius from mid-pregnancy to shortly after delivery (41,42) , whereas others did not (39,40) .…”
Section: Calcium Intake Absorption and Balancementioning
confidence: 99%
“…Table 4 presents data on mean change in aBMD or BA-adjusted BMC from early lactation to after breast-feeding had stopped (8,71,82) , and Table 5 presents changes in aBMD from early lactation to after the resumption of menses (41,67,102) . In general, these studies showed either no significant net difference or an increase in bone mineral in BF women relative to 2 weeks postpartum at most skeletal sites other than the femoral neck.…”
Section: Calcium Intake Absorption and Balancementioning
confidence: 99%
See 1 more Smart Citation
“…The primary mechanism by which calcium is supplied for the support of milk production is the reduction of maternal bone mass. Bone density remains lower during continued lactation, which is independent of parathormone and vitamin D contents (8,13,15,18,19).…”
Section: Discussionmentioning
confidence: 97%